A Generalized Lattice Boltzmann Model for Simulating Axisymmetric Convective Flow in Porous Media - Wang, Zuo; Zhang, Jiazhong; Dang, Nannan; Huang, Biwu (Journal of Vibration Testing and System Dynamics, 2026)
Axisymmetric convective flow in porous media is frequently encountered in nature and industry applications. In recent years, Lattice Boltzmann method has been developed as a powerful tool for such kind of flow and heat transfer. Despite its success in many problems regarding to porous flow, the existing LB model for the axisymmetric thermal flow in porous media at the representative volume scale suffers from a serious drawback. That is, it can not handle the cases where the heat capacitance of porous media varies spatially obviously. In this paper, a generalized LB model for axisymmetric temperature field is proposed to remedy this shortcoming. Chapman-Enskog analysis demonstrates that the energy equation in the cylindrical coordinates system can be recovered by the proposed model. Natural convection in a vertical annulus filled with saturated porous media, natural convection in a vertical annulus without porous media, have been carried out, and the results predicted by the present LB model agree well with the existing numerical data. More, natural convection in a vertical annulus with spatially varying heat capacitance shows that the present model can address the problem where the heat capacitance varies spatially obviously successfully.